A new class of nonstationary motions of a system of heavy Lagrange tops with a non-planar configuration of the system's skeleton - Chebanov, D.A. (Механика твердого тела, 2011)
For a chain consisting of n heavy Lagrange tops coupled by ideal spherical joints, the existence of a class of nonstationary motions with a non-planar configuration of the chain’s skeleton is proved. Sufficient conditions for existence of these motions are established, and the equations of motion of the chain are reduced to quadratures. Under the assumption that the mass distribution of the bodies forming the chain is given, it is shown how they have to be coupled so that the motions of interest could be realized. Some properties of the new motions are discussed.